The Role of Gender in Pay-What-You-Want Contexts. (April 2021) - Santana, Shelle; Morwitz, Vicki G.
This research highlights how gender shapes consumer payments in pay-what-you-want contexts. Four studies involving hypothetical and real payments show that men typically pay less than women in pay-what-you-want settings, due to gender differences in agentic versus communal orientation. Men approach the payment decision with an agentic orientation, and women approach it with a communal orientation. These orientations then shape payment motives and ultimately affect payment behavior. Because agentic men are more self-focused, their payment decisions are motivated by economic factors, resulting in lower payments. Conversely, communal women are more other-focused, and their payment decisions are motivated by both social and economic factors, resulting in higher payments. The findings additionally highlight how sellers can use marketing communications to increase the salience of social payment motives and demonstrate that by doing so, marketers can increase how much men pay without altering how much women pay in pay-what-you-want settings.